Penerapan Manpower Planning dalam Pembiayaan Pendidikan untuk Mengatasi Pengangguran - Hartono; Wahyuni, Sri; Nurkolis Nurkolis (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Unemployment among high school and university graduates in Indonesia remains a structural problem. One of the main causes is the mismatch between the education system and labor market needs. This article aims to explain the application of manpower planning in educational financing as a strategy to address the gap. This research uses a descriptive-qualitative approach through literature study and policy review. The analysis focuses on the implementation of manpower planning, including labor demand projections, competency-based curriculum development, and reorientation of educational funding policies toward priority sectors. The findings show that manpower planning can align educational outputs with labor market needs, improve education budget efficiency, and reduce educated unemployment. In conclusion, implementing manpower planning in education financing is a strategic step that policymakers must adopt to develop a more adaptive and productive education system.